THE CORRELATION AMONG SELF-CONCEPT, READING ATTITUDE AND READING COMPREHENSION ACHIEVEMENT THE SIXTH SEMESTER OF ENGLISH EDUCATION STUDY PROGRAM STUDENTS OF PGRI UNIVERSITY PALEMBANG - Ferri Hidayad (ELTE Journal (English Languange Teaching and Education), 2015)
AbstractThis study was aimed at finding out (1) whether or not there was a correlation between students’ self-concept and reading attitude? (2) whether or not there was a correlation between students’ reading attitude and reading comprehension achievement? (3) whether or not there was contribution of students’ self-concept to reading attitude and reading comprehension achievement? The population of this study was the Sixth Semester Of English Study Program 193 students. From population, 60 students were represented as the samples. The samples were taken using Stratified Random Sampling. The data distribution were considered normal. It was proved by statistic calculation of normality test which shows that p-output (0.034, 0,200, and 0,040). Then based on the calculation of Levene Statistic, it was found that p-value is higher than α (0.05). Based on the result of statistic calculation using correlation. It was found the significant value (r) between students’ self-concept and reading attitude was 0.122 which more than α (0.05). It means that H1 was received. While the significant value (r) between students’ reading attitude and reading comprehension 0.290 which also more than α (0.05). It means that H2 was accepted. It was also found contribution of self-concept to reading attitude (r2) was 15 %, while contribution of reading attitude to reading comprehension achievement was 84 %. It means H3 was received and H0 was rejected. Keyword: Self-concept, Reading Attitude and Reading Comprehension Achievement